Estudo do conversor zeta em condução simultânea dos semicondutores aplicada à alimentação de LEDs de potência - Pedrollo, Guilherme Rodrigues (2015)
This work presents the simultaneous conduction mode (SCM), which is applied to the operation of the Zeta converter. This mode has the ability to implement an ideal power factor corrector (PFC) employing only one feedback control loop. In SCM, the current in the main switch and in the diode flows simultaneously within one of the operation stages. In SCM, the power converter presents characteristics of both conduction modes: continuous conduction mode (CCM) and discontinuous conduction mode (DCM). In SCM, the currents in the inductors of the power converter are never nullified, which is a typical behavior of the CCM. Nevertheless, the SCM does that while obtaining an ideal PFC with just one control loop. The SCM maintains its features, regardless of its control variable being the output current or the output voltage of the power converter. The solely application of a fixed duty cycle controller is enough to attain all these advantages, which is usually a feature of the DCM for PFCs of the flyback family. In order to validate the proposed technique, a complete study of the Zeta converter working in this new operation mode was performed.This study has included a qualitative and a quantitative power converter analysis. These analyses resulted in the development of a design methodology for the Zeta power converter working as a PFC in the SCM. In order to validate the present study, a prototype of the Zeta PFC for operation in the SCM was designed and built. This prototype was developed, as a case of study, to drive a power LED lamp (180°W). Thus, it was obtained the desired experimental confirmation for the research. The main advantage of the SCM, in comparison to the CCM, lies in its ability to maintain the input current of the PFC sinusoidal and in phase with the input voltage, which is imposed by the mains through the use of just a single PWM controller with fixed duty cycle. These results have, also, shown that the current peaks in the main semiconductors of the power converter are lower than their respective values in the DCM. However, this new operation mode results in the increase of the voltages on the main switch and diode in relation to the conventional power converter operation. The research of the application of the proposed method to other power converters is suggested to further works.